Fbw7 Inhibits the Progression of Activated B-Cell Like Diffuse Large B-Cell Lymphoma by Targeting the Positive Feedback Loop of the LDHA/lactate/miR-223 Axis - Yao, Su; Guo, Tairan; Zhang, Fen; Chen, Yu; Xu, Fangping; Luo, Donglan; Luo, Xinlan; Lin, Danyi; Chen, Wendan; Li, Zhi; Liu, Yanhui (Frontiers in Oncology, 2022)
Background:F-box and WD repeat domain-containing 7 (Fbw7)is well known as atumor suppressor and ubiquitin ligase which targets a variety of oncogenic proteins for proteolysis. We previously reported that Fbw7 promotes apoptosisin diffuse large B-cell lymphoma (DLBCL) through Fbw7-mediated ubiquitination of Stat3.This study aimed to identify the mechanism of Fbw7-mediated aerobic glycolysis reprogramming in DLBCL. Methods: Expression levels of Fbw7 and Lactate Dehydrogenase A (LDHA) in human DLBCL samples were evaluated by immunohistochemistry. Crosstalk between Fbw7 and LDHA signaling was analyzed by co-immunoprecipitation,ubiquitination assay, western blotting and mRNA qualitative analyses. In vitro and in vivo experiments were used to assess the effect of the Fbw7-mediated LDHA/lactate/miR-223 axis onDLBCL cells growth. Results: Fbw7 could interact with LDHA to triggerits ubiquitination and degradation, and lactate negatively regulated Fbw7 viatrigging the expression of miR-223, which targeted Fbw7 3’-UTR to inhibitits expression. In vivo and in vitroexperiments revealed that miR-223 promoted tumorgrowth and that the effects of miR-223 on tumor growth were primarily related to the inhibition of Fbw7-mediated LDHA’s ubiquitination. Conclusions: We demonstrated that the ubiquitin-ligase Fbw7 played a keyrole in LDHA-related aerobic glycolysis reprogramming in DLBCL.Our study uncovers a negative functional loop consisting of a Fbw7-mediated LDHA/lactate/miR-223 axis,which may supportthe future ABC-DLBCL therapy by targetingLDHA-related inhibition.